2018
DOI: 10.1021/acs.jpcc.7b07502
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of the Interactions between Graphene Oxide and Amine-Functionalized Carbon Nanotube

Abstract: We applied plane-wave density functional theory to study the effects of chemical functionalizations of graphene and carbon nanotube (CNT) on the properties of graphene–CNT complexes. The functionalizations of graphene and CNT were modeled by covalently attaching oxygen-containing groups and amines (NH2), respectively, to the surfaces of these carbon nanomaterials. Our results show that both dispersion energy and hydrogen bonding play crucial roles in the formation of complexes between graphene oxide (GO) and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Because of the relatively large system size (containing up to 259 atoms), only the Γ-point (k = 0) of the Brillouin zone was sampled. 43,44 Furthermore, the convergence test with respect to the k-point sampling (1 × 1 × 1 vs 3 × 3 × 1 k-points tested) confirmed that Γpoint sampling was sufficient to achieve the convergence of computed interaction energy within 0.02 eV/nm. In addition, denser k-point grids were used for the calculations of electronic DOS.…”
Section: Methodsmentioning
confidence: 64%
See 2 more Smart Citations
“…Because of the relatively large system size (containing up to 259 atoms), only the Γ-point (k = 0) of the Brillouin zone was sampled. 43,44 Furthermore, the convergence test with respect to the k-point sampling (1 × 1 × 1 vs 3 × 3 × 1 k-points tested) confirmed that Γpoint sampling was sufficient to achieve the convergence of computed interaction energy within 0.02 eV/nm. In addition, denser k-point grids were used for the calculations of electronic DOS.…”
Section: Methodsmentioning
confidence: 64%
“…This approach of combining the vdW-DF2 functional with the pseudopotentials designed for the PBE functional has been successfully employed in several previous studies. [40][41][42][43] To validate our computational approach, we first calculated the structures of pristine CNT, graphene, and the CNT + graphene complex and compared them with the available results (described in Sec. III A).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction energy ( E int ) of the composites is defined as [Eq. ]: trueEint=ELayerA-Linker-LayerB-ELayerA-ELayerB-ELinker …”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectrum of graphene oxide shows the presence of sharp bands at 1734 cm −1 (for C=O stretching), 1620 cm −1 (for C=C stretching), 1224 cm −1 (for C-O-C stretching), 1054 cm −1 (for C-O stretching), and 3421 and 1385 cm −1 for hydroxyl group deformation peak. These band positions indicate the presence of oxygen containing moieties such as carbonyl, carboxylic, epoxy, and hydroxyl in graphene oxide (31,32). The FTIR spectrum of ovalbumin reduced graphene shows a drastic decrease in intensities of all oxygen functionalities peaks at 1734, 3421, and 1385 cm −1 , which corresponds to C=O stretching and OH deformation vibration, respectively.…”
Section: Fourier Transform Infrared (Ftir) Spectroscopymentioning
confidence: 98%